Representing Trauma and the Legacy of Slavery in Contemporary African American Fiction: From Silence to Healing in Yaa Gyasi’s Homegoing (2016) - Abed, Amira Khouloud (AMERICANA E-journal of American Studies in Hungary, 2025)
This paper analyzes Yaa Gyasi’s debut novel, Homegoing (2016), and explores each character's traumatic experiences as a legacy of slavery and the slave trade. The paper delves into the way trauma becomes an ancestral legacy and a burden of the past - an intergenerational trauma - that is transmitted to the descendants over two centuries and studies its impact on different generations of African Americans in the novel. By relying on the insights of Cathy Caruth and Marianne Hirsch, the narrativization of trauma through writing fiction is considered therapeutic, and it provides a space for reconciliation; the paper explores the healing journey of the characters in the novel.